KEPALA SEKOLAH SEBAGAI PENENTU KEBIJAKAN PENDIDIKAN DI SEKOLAH DASAR - Ninik Hidayati; Dian Rustyawati (PREMIERE : Journal of Islamic Elementary Education, 2019)
Head Master of school / madrasah as a leader in an educational institution which is the most important element in the course of the organization of educational institutions. As educational leaders, head master/madrasah has a number of tasks and responsibilities that difficult to regulate and set policy and determine the attitude and the purpose of educational institutions. To be able to do his responsibilities optimally, the head master of school / madrasah need to apply the appropriate leadership style to perform the task and responsibilities as leader of school / madrasah. In order that, the style of a person lead will greatly affect the organization that he leads, whether the influence is positive or negative, on the organization. The some reasons of the success of a leader are experienced, courage, initiative, assertive, thoughtful, fair, have tenacity, have a great spirit, able and willing to undertake full responsibility, can guarantee his teamwork and control of the issue and has deep sympathy and understanding.